2016
DOI: 10.1021/acs.jpcc.6b02023
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Tilt Angles of Adsorbed Aromatic Molecules on Nanoparticle Rattle SERS Substrates

Abstract: Solution-phase nanoparticles are extensively used as surface enhanced Raman scattering (SERS) substrates, but signal intensities depend on dynamic nanoparticle optical properties and stabilities as well as molecular identity and orientation. To evaluate how these contributions influence the detection of aromatic thiols, internally etched silica encapsulated gold-coated silver (IE Ag@Au@SiO2) nanoparticles are used. First, localized surface plasmon resonance (LSPR) spectroscopy is implemented to estimate molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 61 publications
3
49
0
Order By: Relevance
“…Although the EM-enhancement of incident light is considered as the largest contributor to the SERS intensity amplification, the chemical enhancement cannot be totally ruled out. Many studies have demonstrated that the SERS efficiency is closely related to non-EM factors, such as the adsorption of the analyte to the Au surface 76 77 , and the adsorbed analyte molecular orientation 78 . As mentioned earlier, the surface OA ligand in the Au NP monolayer has a different chain conformation than that of the alkylamine-Au NP film.…”
Section: Resultsmentioning
confidence: 99%
“…Although the EM-enhancement of incident light is considered as the largest contributor to the SERS intensity amplification, the chemical enhancement cannot be totally ruled out. Many studies have demonstrated that the SERS efficiency is closely related to non-EM factors, such as the adsorption of the analyte to the Au surface 76 77 , and the adsorbed analyte molecular orientation 78 . As mentioned earlier, the surface OA ligand in the Au NP monolayer has a different chain conformation than that of the alkylamine-Au NP film.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in main text, 4MBA molecule is adsorbed on the surface of Ag/Ag-doped TiO 2 substrate by Ag-S bond, and the benzene ring and COOH group can rotate round the bond. Normally, 4MBA molecules should orient to the surface at an approximate angle of 57°for a close-packed selfassembled monolayers 60 . During light irradiation, the reorientation of 4MBA molecules are subject to the actions of electric-field force, damping fore, and restoring force.…”
Section: Methodsmentioning
confidence: 99%
“…It can be found that interaction of cytosine through both N and O atoms with Ag 20 reproduce the experimental SERS spectra better than others. It should be mentioned that the dependence of SERS spectra on the orientations of adsorbent has been demonstrated previously . At last but not least, in order to find the dependence of shape of spectrum to overtone excitation, the Cyt─Ag 20 SERS spectrum was obtained (by considering the overtone excitations), and slight variation and modification in the intensity of high‐frequency region (>1,200 cm ‐1 ) was found in Figure S9.…”
Section: Resultsmentioning
confidence: 59%